2014
DOI: 10.1080/19371918.2014.938393
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Work-Related Musculoskeletal Disorders on the Link between Psychosocial Factors and Absenteeism among Administrative Workers

Abstract: This study aimed to investigate the association between psychosocial factors (i.e., job demand, decision latitude, social support, physical environment, and personal risk factors), work-related musculoskeletal disorders (WRMDs), and productivity as measured by workers' perceived absenteeism. Data were collected from the selected administrative workers (administrative assistant) and analyzed using cross tabulation. The results indicate that all psychological factors are not significantly associated with WRMDs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
2
3
1
Order By: Relevance
“…In explaining the cause, it can be said that the muscular system of men is stronger than women. This result is consistent with results of previous studies that revealed women are more at risk of shoulder pain (5, 7). Our results showed a significant relationship between marital status and shoulder pain; therefore, the occurrence risk of shoulder pain in married people was about 2 times more than single people and it may be because of the difficulties of married life and increasing individual responsibility.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In explaining the cause, it can be said that the muscular system of men is stronger than women. This result is consistent with results of previous studies that revealed women are more at risk of shoulder pain (5, 7). Our results showed a significant relationship between marital status and shoulder pain; therefore, the occurrence risk of shoulder pain in married people was about 2 times more than single people and it may be because of the difficulties of married life and increasing individual responsibility.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, with 10 kilos increase of weight, the occurrence risk of neck pain will be increased 62%. The results of previous studies showed the significant impact of this factor on the occurrence of musculoskeletal disorders, but none mentioned gave an explanation as clearly as that which was stated in this study (5, 6, 19). Although in this study it was shown that for each centimeter increase in height the risk of neck pain occurrence would be increased 1%, unlike some previous studies, this amount was not statistically significant (2, 5, 17).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…35 In previous studies, MSCs played a role as mediators in the relationship between workload, psychological work-related factors, and presenteeism. 36 Consistent with our expectations, our results partially revealed that the relationship between job demands and presenteeism was mediated by MSCs and that job resources (in the form of job control) moderated the relationship between MSCs and presenteeism such that a high level of job resources attenuated the effects of MSCs on presenteeism.…”
Section: Discussionsupporting
confidence: 90%